Assessment of value creation in private equity: the acquisition of Burger King by 3G Capital - Hoene, Daniel Jobst Elmar (2016)
This thesis elaborates the creation of value in private equity and in particular analyzes value creation in 3G Capital’s acquisition of Burger King. In this sense, a specific model is applied that composes value creation into several drivers, in order to answer the question of how value creation can be addressed in private equity investments. Although previous research by Achleitner et al. (2010) introduced a specific model that addresses value creation in private equity, the respective model was neither applied to an individual company, nor linked to indirect drivers that explain the dynamics and rationales for the creation of value. In turn this paper applies the quantitative model to an ongoing private equity investment and thereby provides different extensions to turn the model into a better forecasting model for ongoing investments, instead of only analyzing a deal that has already been divested from an ex post perspective. The chosen research approach is a case study about the Burger King buyout that first includes an extensive review about the current status of academic literature, second a quantitative calculation and qualitative interpretation of different direct value drivers, third a qualitative breakdown of indirect drivers, and lastly a recapitulating discussion about value creation and value drivers. Presenting a very successful private equity investment and elaborately demonstrating the dynamics and mechanisms that drive value creation in this case, provides important implications for other private equity firms as well as public firms in order to develop their proprietary approach towards value creation.